(untitled) (Bangladesh Heart Journal, 2024)
Dyslipidemia is a significant risk factor for atherosclerotic cardiovascular diseases, including ischemic heart disease. However, hypercholesterolemia patients without a history of clinical ischemic heart disease (IHD) may experience chest pain that presents diagnostic and management challenges. This review aims to summarize the existing literature and assess the prevalence of chest pain in this specific patient without having previous heart disease. Bangladesh Heart Journal 2024; 39(1): 57-62